The Use of Fatty Acids in the Flotation of Rare Earth Oxides from Low Grade Tailings - G. B. Abaka-Wood (International Mineral Processing Congress, 2018)
"The versatility of froth flotation has made it vital in the beneficiation of rare earth elements (REE) minerals from either high or low grade ores of complex mineralogy. There has been a significant increase in the tonnage of rich iron oxide tailings obtained from extraction of primary commodities such as copper and gold in Australia, which have been identified to have very low grade rare earth oxides (REO) (= 1%). There is a vast knowledge gap in the upgrade of REO from such tailings. The aim of this research is to investigate the feasibility of the use of fatty acids for the upgrading of REO from selected iron-oxide rich tailings. Two forms of fatty acid collectors (oleic acid and sodium oleate) were employed in this investigation. Bench scale flotation tests were carried out using a Denver D-12 cell.The effects of pulp pH, fatty acid dosage, particle size distribution (-150 +75 µm, -75 +38 µm and -38 µm) and conventional depressants (sodium silicate and starch) dosage on flotation recovery of REO were investigated. A comparison of the flotation results indicated that sodium oleate was the more efficient fatty acid for REO flotation at all the pulp pH investigated. The flotation performance is demonstrated to be particle size-dependent. The results on the effect of depressants dosage indicated that both sodium silicate and starch were unselective in reducing the recovery of hematite (Fe2O3) and quartz (SiO2) with corresponding decrease in REO recovery. Generally, Fe2O3 and SiO2 formed substantial contents of the flotation concentrates obtained, both in the absence and presence of depressants, which indicates liberation is a major challenge in achieving selective REO upgrade and recovery.The flotation tests carried out on the iron-oxide rich tailings suggest the possibility of REO upgrade using fatty acids, although particle size distribution and minerals liberation are key limiting factors in achieving selective REO upgrade and recovery."